2016
DOI: 10.5897/ijpc2015.0311
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits as predictors of Facebook use

Abstract: This study explores the personality factors behind Filipino college students' social media usage. Using descriptive-correlational design, a random sample of 338 Filipino undergraduate students, between ages of 16 to 22, was employed to generate relationships and understand predictions among factors derived from NEO Personality Inventory and Facebook Intensity Scale. Results indicated that respondents tend to be more neurotic and less agreeable but conscientious. Regression analysis model delineated that among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Stemmed from computer-mediated communication research, the intensity of Facebook use refers to the extent one is emotionally connected and actively engaged in activities on Facebook (Acopio and Bance, 2016). In previous studies, Petter et al (2013) reviewed 140 articles based on the information systems success model and found that users' trust toward online community platforms could significantly increase their behavioral intentions such as continued usage and user satisfaction.…”
Section: Effects Of Trust and Distrust On The Intensity Of Facebook Usementioning
confidence: 99%
“…Stemmed from computer-mediated communication research, the intensity of Facebook use refers to the extent one is emotionally connected and actively engaged in activities on Facebook (Acopio and Bance, 2016). In previous studies, Petter et al (2013) reviewed 140 articles based on the information systems success model and found that users' trust toward online community platforms could significantly increase their behavioral intentions such as continued usage and user satisfaction.…”
Section: Effects Of Trust and Distrust On The Intensity Of Facebook Usementioning
confidence: 99%
“…Up to 56 British participants and up to 144 German individuals take part in the survey. The use of SNSs is defined with the duration of membership in years, number of contacts and time spend per day in average per minutes [32]. The details are presented in Table 2.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Furthermore, Bergh (2009) confirmed that personality is probably one of the most significant fields to be regarded in the research on human nature and differences, as well as similarities between individuals. The best personality domain can be best defined by the Five Factor Model (FFM) using the Big Five Personality Dimensions (Acopio & Bance 2016). This model conceptualises the hierarchy of personality traits in a series of five simple dimensions, namely, neuroticism, extraversion, openness to experience, agreeableness and conscientiousness (Ali 2019;Mhlanga 2019;Szcześniak, Sopińska & Kroplewski 2019).…”
Section: Introductionmentioning
confidence: 99%